A study of clinical profile of patients undergoing endonasal endoscopic dacryocystorhinostomy without stenting in a teaching hospital of Western Gujarat - Sorathiya, Rashmi; Desai, Nisarg; Hirani, Narendra; Khilnani, Ajeet Kumar; Bodat, Ronak; Karathia, Neha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic dacryocystitis is commonly treated with dacryocystorhinostomy (DCR). The aim of the study was to analyzed the clinical profile of patients suffering from distal Nasolacrimal duct (NLD) blockage and outcomes of EnDCR without stenting in patients with chronic dacryocystitis. Methods: This prospective observational study consisted of 50 patients who underwent EnDCR without stenting at ENT department of Gujarat Adani Institute of Medical Sciences during the period of October 2019 to September 2021, after taking IEC consent. All patients with distal NLD blockage were included in study. Pre-operative, intra-operative and post-operative details were recorded as per pre-validated proforma and data was analyzed using Microsoft excel sheets. Results: Watery discharge from eye was most common chief complaint (76%) during presentation followed by watery discharge and swelling over medial end of eye both (20%) and swelling over medial end of one eye (4%). Most common duration of chief complaint was between 3 to 12 months. In our study, out of 50 patients, 31 cases were operated under local anesthesia and 19 were operated under general anesthesia. Out of 50 operated cases, only 3 patients had stenosis of ostium at 3-month follow-up. Overall success rate of endoscopic endonasal DCR without stenting was 94%. Conclusions: The success rate of endonasal dacryocystorhinostomy without stenting is as high as that of external dacryocystorhinostomy and endonasal DCR with stenting without the disadvantages of either one.